2006
DOI: 10.1183/09031936.06.00021305
|View full text |Cite
|
Sign up to set email alerts
|

The effects of farming and birth order on asthma and allergies

Abstract: A farm childhood is apparently protective in allergic disease, but studies of this issue in Europe have been confined to particular types of farming practice. This study addressed whether or not this effect was generalisable.A cross-sectional survey of 800 schoolchildren living in rural Crete was undertaken. Standard questions relating to allergic disease were included and atopy was measured through skin-prick tests involving 10 local aeroallergens.The prevalence of atopy was 24%, but associated symptoms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 20 publications
2
14
1
1
Order By: Relevance
“…In the rural areas of this study, inhabitants have little contact with large animals and thus constitute an entirely different rural milieu than the one reported by studies from central Europe (36,37).…”
Section: Allergen Exposurementioning
confidence: 70%
“…In the rural areas of this study, inhabitants have little contact with large animals and thus constitute an entirely different rural milieu than the one reported by studies from central Europe (36,37).…”
Section: Allergen Exposurementioning
confidence: 70%
“…The outcome variables that were evaluated in relation to diet were: wheezing ever, wheezing ever with atopy, current wheezing, nocturnal dry cough in the last 12 months apart from a common cold/flu, allergic rhinitis ever, allergic rhinitis ever with atopy, current allergic rhinitis, current seasonal allergic rhinitis and atopy. Multivariate logistic regression models were performed to examine the association between fruit and vegetable consumption (in three levels, using ''never'' as reference) and the outcome variables, after adjusting for the following confounders: age (in years; three categories: 7-12, [13][14][15][16][17][18], sex, body mass index (BMI, age-and sex-adjusted cut off points for normal, overweight, obese children), 19 parental asthma (yes, no) and number of older siblings (0, 1, 2, 3+). Logistic regression was performed to examine the association between the outcome variables and the consumption of specific nutrients included in the Mediterranean diet index and, separately, with the overall adherence to the Mediterranean diet (in three levels, using ''low'' level as reference).…”
Section: Discussionmentioning
confidence: 99%
“…All school children aged between 7 and 18 years were invited to participate in the study (n = 857). 15 Permission was obtained from the appropriate ethical committees (Venizelion Hospital in Heraklion, Royal Brompton Hospital in London, Ministry of Education in Greece). All parents gave written informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies assessing birth order and subsequent allergy development reveal a clear protective benefit of siblings [24,25,26,27,28], supported by a meta-analysis of 53 studies, that showed that the odds of eczema, hayfever, asthma or sensitisation are reduced by 28-56% in children with ≥3 siblings [29]. …”
Section: Parental and Periconceptional Factorsmentioning
confidence: 97%